Psychological characterization of romantic passion - Sánchez Aragón, Rozzana (Pensando Psicología, 2018)
Introduction: the romantic passion as a cultural universal has particular nuances that define its different phases: attraction, falling in love, obsessive and desperate love. Along with its conceptualization, there are variables that relate to its experience, such as the historic-socio-cultural premises that create expectations about it, the attributes of sexual personality perceived in the passion object, the behaviors and strategies of seduction used during the passionate event, as well as the sexual satisfaction resulting from its consummation.Objective: the purpose of this research was to characterize each of the passion phases based on the variables related to its experience.Method: we worked with a non-probabilistic sample of 495 residents of Mexico City between 15 and 58 years old who recognized having lived a romantic passion.Results: after some Pearson’s correlation analysis, we identify the effects common to the participants in the description of their experience for the phases, as well as the differential way of feeling romantic passion for men and women.Conclusion: the present investigation was able to broad the conception of the phases of passionate love based on the data related to the PHSC’S, sexual personality, seduction strategies and sexual satisfaction in a Mexican sample. Likewise, what distinguished men and women regarding the experience of these phases was identified and  discussed according to the norms and beliefs of the Mexican culture.
Keywords: culture; obsession; romantic passion; sexual personality; seduction